Association between neighbourhood walkability and metabolic risk factors influenced by physical activity: a cross-sectional study of adults in Toronto, Canada. Issue 4 (8th April 2017) - Loo, C K Jennifer; Greiver, Michelle; Aliarzadeh, Babak; Lewis, Daniel
Abstract : Objective: To determine whether neighbourhood walkability is associated with clinical measures of obesity, hypertension, diabetes and dyslipidaemia in an urban adult population. Design: Observational cross-sectional study. Setting: Urban primary care patients. Participants: 78 023 Toronto residents, aged 18 years and over, who were formally rostered or had at least 2 visits between 2012 and 2014 with a primary care physician participating in the University of Toronto Practice Based Research Network (UTOPIAN), within the Canadian Primary Care Sentinel Surveillance Network (CPCSSN). Main outcome measures: Differences in average body mass index (BMI), systolic and diastolic blood pressure, fasting blood glucose, haemoglobin A1c (HbA1C), total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein and triglyceride between residents in the highest versus the lowest quartile of neighbourhood walkability, as estimated using multivariable linear regression models and stratified by age. Outcomes were objectively measured and were retrieved from primary care electronic medical records. Models adjusted for age, sex, smoking, medications, medical comorbidities and indices of neighbourhood safety and marginalisation. Results: Compared with those in the lowest walkability quartile, individuals in the highest quartile had lower mean BMI (−2.64 kg/m 2, 95% CI −2.98 to −2.30; p<0.001), systolic blood pressure (−1.35 mm Hg, 95% CI −2.01 to −0.70; p<0.001), diastolic blood pressure (−0.60 mm Hg, 95% CI 1.06 to −0.14; p=0.010) and HbA1c (−0.063%, 95% CI −0.11 to −0.021; p=0.003) and higher mean HDL (0.052 mmol/L, 95% CI 0.029 to 0.075; p<0.001). In age-stratified analyses, differences in the mean BMI were consistently observed for adults aged 18 to under 40 (−4.44 kg/m 2, 95% CI −5.09 to −3.79; p<0.001), adults aged 40–65 (−2.74 kg/m 2, 95% CI −3.24 to −2.23; p<0.001) and adults aged over 65 (−0.87 kg/m 2, 95% CI −1.48 to −0.26; p=0.005). Conclusions: There was a clinically meaningful association between living in the most walkable neighbourhoods and having lower BMI in adults of all ages.